2017
DOI: 10.1051/shsconf/20173300084
|View full text |Cite
|
Sign up to set email alerts
|

User-Generated Contents in Facebook, Functional and Hedonic Brand Image and Purchase Intention

Abstract: Abstract. User-Generated Contents is a type of brand-related communications on social media platforms. User-Generated Contents (UGC) offers consumers the opportunity of sharing their experiences, contribute their opinion and communicate with other. This implies that brand managers no longer have solitary control in managing the brand images of their brands. Therefore, this study set out to examine the effect of user-generated contents on hedonic brand image and functional brand. Also, the study determines how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
(16 reference statements)
0
7
0
1
Order By: Relevance
“…Hedonic brand image instead refers to the perceptions, feelings, or meaning that consumers create and associate with the brand. Researchers [43] have provided insight on the importance of the functional and hedonic brand image to brand managers. Findings revealed that both functional and hedonic brand image have a significant influence on brand purchase intention.…”
Section: The Relationships Between Brand Image Flow and Purchase Intmentioning
confidence: 99%
See 1 more Smart Citation
“…Hedonic brand image instead refers to the perceptions, feelings, or meaning that consumers create and associate with the brand. Researchers [43] have provided insight on the importance of the functional and hedonic brand image to brand managers. Findings revealed that both functional and hedonic brand image have a significant influence on brand purchase intention.…”
Section: The Relationships Between Brand Image Flow and Purchase Intmentioning
confidence: 99%
“…When investigating the relationship between luxury consumption and brand communication, taking global consumers as the target group, it is found that the history, technology, product integrity, and brand reputation of brand communication will affect consumers' purchase intention; and that brand communication has a significant positive impact on purchase intention [54]. Previous studies have shown that consumers will make judgments that affect their purchase behavior through the hedonic and functional attributes of brand communication, which can effectively enhance their willingness to buy [43]. In the study of brand communication of chain hotels, it is believed that the knowledge and values related to brand can be spread through the digital environment, so as to strengthen the loyalty and trust of the relevant public [55].…”
mentioning
confidence: 99%
“…With regards to the interactive features and the ubiquitous nature of social media platforms, the possibility of a daily and frequent encounter, engagement and feedback between consumers and brands are increased. These subsequently, increase the level of brand awareness in terms of recall and recognition, improve positive image of the brand and ultimately shape the attitude of the consumers towards the brand (Adetunji, Sabrina, & Sobhi, 2017). Therefore, this study recommends that, brand managers of automotive brands should continue their employment of social media platforms as an important effort for building and maintaining their brand equity.…”
Section: Discussion and Implicationmentioning
confidence: 95%
“…As such, the study contributes to the body of knowledge in determining the effect of social media in the realm of CBBE development and evoking favorable behaviors of consumers. The study also proffers important practical recommendations to marketing communication practitioners, brand managers and marketers of automotive brands in Malaysia to maximize the potentials of social media marketing communications in enhancing the images of their brands (Adetunji et al, 2017). Most specifically because social media's popularity continues to increase among Malaysians, marketers and brand managers should take note of the fact that Social Media Word-of-Mouth such as videos, images and comments on Facebook, YouTube, Instagram and Twitter are important for developing CBBE.…”
Section: Discussionmentioning
confidence: 96%
“…The study offers a number of theoretical contributions, which include the conclusion that the impact of Social Media Word-of-Mouth is more useful in enhancing and developing CBBE than its impact on Consumer Response. More so, understanding the impact of UGC and Word-of-Mouth on brand equity has a practical importance, considering the level at which consumers are adopting social media platforms to search for brand-related information lately (Adetunji, Sabrina, & Sobhi, 2017). As such, brand managers especially the brand managers and marketers of automotive brands in Malaysia should pay more attention to engaging and relating with their consumers through social media platforms in order to improve the acceptance of their brands and to increase favorable behaviors and responses for their consumers.…”
Section: Discussionmentioning
confidence: 99%